Pembelajaran Online berbasis Have Fun Learning dengan Penilaian Modern pada Era Pandemi Covid-19 - Fathan Mubina Dewadi; Chepi Reynaldi; Muhammad Rifqi Putra Syah (JECED : Journal of Early Childhood Education and Development, 2021)
for an existing system, so with an outbreak like this, especially in the academic world, there needs to be a breakthrough when learning media uses an online system. This research is classified as qualitative because it involves qualitative information because this research refers to evidence of general information without any statistical and quantitative calculations. Conclusion on This research is by taking a good approach to students, the KBM process goes well. The role of educators who are patient and skilled makes students comfortable in learning and one of the important innovations is remedial which is required so that students continue to be challenged. Suggestions for this research is to immediately apply it on a more complex mass scale and research on socio-cultural studies regarding the character of students is needed.